Analisa Dan Pengembangan Sistem Informasi Distribusi Dan Penjualan Cv Jogja Konveksi - Triyolla Ivandina; Yuhandri; Aggy Pramana Gusman (Jurnal Teknologi, 2020)
The system applied by CV Jogja Convection which is one of the distributors in the city of Padang. In the data processing information system that supports sales which includes goods data, customer or customer data, and others. The design of this system is one of the choices to help the distribution of goods such as sales at CV Jogja Convection. The information system created is based on a website and has a function as a medium for the distribution of goods CV Jogja Convection. This web-based information system can speed up accurate data entry and fast search processes in sales information systems in particular.